2016
DOI: 10.1111/tbed.12504
|View full text |Cite
|
Sign up to set email alerts
|

Improved Strategy for Molecular Characterization of African Swine Fever Viruses from Sardinia, Based on Analysis of p30, CD2V and I73R /I329L Variable Regions

Abstract: African swine fever virus (ASFV) is the aetiological agent of a highly lethal haemorrhagic disease affecting pigs that inflicts significant economic damage on the swine industry. ASF is present in many African countries, in several eastern and central European countries and in Sardinia (Italy). Sequence analyses of variable genomic regions have been extensively used for molecular epidemiological studies of ASFV isolates. Previous sequencing data of genes that codify for viral protein p54, p72 and the central v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 26 publications
3
87
1
Order By: Relevance
“…Similarly, based on a sequence comparison with the protein encoded by the EP402R gene, Sanna et al. () observed a temporal division of ASFV strains collected in Sardinia from 1978 to 2014, but no differences in isolates recovered from wild boar and domestic pigs. Critically, Frączyk et al.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, based on a sequence comparison with the protein encoded by the EP402R gene, Sanna et al. () observed a temporal division of ASFV strains collected in Sardinia from 1978 to 2014, but no differences in isolates recovered from wild boar and domestic pigs. Critically, Frączyk et al.…”
Section: Assessmentmentioning
confidence: 99%
“…The CD2v transmembrane potential is required for haemadsorption of red blood cells around infected macrophages and for the adhesion of extracellular virions to erythrocytes and consequent viral dissemination. Further, it is known that expression of the CD2v protein enhances virus replication in the tick vector (Sanna et al., ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related ASFV isolates can be distinguished through sequence analysis of tandem repeats in the central variable region within the B602L gene (Gallardo et al., ) or the intergenic region between the I73R and I329L genes at the right end of the genome (Gallardo et al., ). Several other gene regions, such as the E183L encoding p54 protein, the CP204L encoding p30 protein and the protein encoded by the EP402R gene (CD2v), have been proved as useful tools to analyse ASFVs from different locations to track the virus spread (Gallardo et al., ; Gallardo et al., ; Sanna et al., ). The genetic characterization approach is not related to biological properties.…”
Section: Asf Virus Characteristicsmentioning
confidence: 99%
“…Based on nucleotide sequencing of the p72 capsid protein gene, 22 genotypes (I to XXII) have been distinguished, but additional genomic regions have been suggested for increased resolution (2, 3). Genetic analysis of ASFV isolates from Sardinia revealed that they all belong to the p72 genotype I, with only minor variations within the B602L and the EP402R genes (4, 5). To better distinguish between these closely related isolates, comparative analysis of near-full-length or complete viral genome sequences is required.…”
Section: Genome Announcementmentioning
confidence: 99%